Система фізико-хімічних методів аналізу як інструмент управління якістю в процесі виробництва виноградних вин - Іукурідзе, Елдар Жорайович; Кучеренко, Володимир Михайлович; Ткачкенко, Оксана Борисівна; Лозовська, Тетяна Сергіївна (НТУ "ХПІ", 2015)
Представлено аналіз основних систем контролю якості у виробництві столових виноградних вин, переваги та недоліки в реальних умовах виробництва, інформативність показників в аспекті прийняття технологічних рішень. Обговорено результати комплексної оцінки вин, вироблених з використанням різних систем внутрішнього контролю та управління якістю. Встановлено, що введення додаткових показників контролю не впливає на рівень органолептичної оцінки вина і значення основних показників якості, визначених існуючою нормативною документацією.

Quality wine - is the extent to wine organoleptic perception of the physical and chemical parameters that characterize a particular type of wine. Analysis of existing monitoring systems in the world production of wines of the highest category of quality showed that the responsibility for the implementation process fully falls upon the manufacturer, which is the main quality of the finished product, and consequently the reputation of the manufacturer. This approach is new for our country. The manufacturer declares that the high quality of its products should be able to develop a system of internal controls in accordance with terroir characteristics that affect the quality of the finished product, or use an existing control system under the current legislation. The appearance in the legislative field of Ukraine of a new category of wines - controlled items originally set scientists on the appropriateness division control.
The system of physical and chemical methods of analysis as a tool for quality control in the production of wines
Keywords: система показників; контроль якості; органолептична оцінка вина; нормативна документація; grape; system of indicators